2007
DOI: 10.1016/j.virol.2006.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Variola virus IL-18 binding protein interacts with three human IL-18 residues that are part of a binding site for human IL-18 receptor alpha subunit

Abstract: Interleukin-18 (IL-18) plays an important role in host defense against microbial pathogens. Many poxviruses encode homologous IL-18 binding proteins (IL-18BP) that neutralize IL-18 activity. Here, we examined whether IL-18BP neutralizes IL-18 activity by binding to the same region of IL-18 where IL-18 receptor (IL-18R) binds. We introduced alanine substitutions to known receptor binding sites of human IL-18 and found that only the substitution of Leu5 reduced the binding affinity of IL-18 with IL-18BP of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 32 publications
3
32
0
1
Order By: Relevance
“…Lys-53 also forms a hydrogen bond and a salt bridge, respectively, with Glu-69 and Glu-77 of ectvIL-18BP, effectively lodging hIL-18 Lys-53 into a remarkably secure position. These intimate interactions form a network of stabilizing forces at binding site A, fully explaining some previous mutagenesis studies on various IL-18BPs and hIL-18 (14)(15)(16)(17). These studies identified Tyr-53 and Phe-67 of ectvIL-18BP and Lys-53 of hIL-18 as residues that contribute most significantly to complex formation between these 2 molecules.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Lys-53 also forms a hydrogen bond and a salt bridge, respectively, with Glu-69 and Glu-77 of ectvIL-18BP, effectively lodging hIL-18 Lys-53 into a remarkably secure position. These intimate interactions form a network of stabilizing forces at binding site A, fully explaining some previous mutagenesis studies on various IL-18BPs and hIL-18 (14)(15)(16)(17). These studies identified Tyr-53 and Phe-67 of ectvIL-18BP and Lys-53 of hIL-18 as residues that contribute most significantly to complex formation between these 2 molecules.…”
Section: Resultssupporting
confidence: 69%
“…The current crystal structure displays a 1,930-Å 2 buried solventaccessible area that is much larger than that observed in the IL-1␤-IL-1R␣ complex at site II (1,000 Å 2 ) (18). Assuming that hIL-18 binds its receptor ␣-subunit in mode similar to that observed in the IL-1␤-IL-1R␣ complex, our structure suggests a much tighter binding by IL-18BP compared with its receptor, which is further supported by binding studies (8,15,16). Therefore, the current structure supports a general inhibition mechanism by which IL-18BP neutralizes hIL-18 through competition with IL-18R␣ at a common binding site, thus antagonizing IL-18 and mitigating its effects on IFN-␥ production and host immune response.…”
Section: Mechanism Of Il-18 Inhibition By Ectvil-18bpsupporting
confidence: 76%
See 2 more Smart Citations
“…The V5 coding sequences in the primers are underlined. The recombinant PCR product was cloned into the EcoRI and AccI sites of pYW31 (14) flanking the green fluorescent protein (gfp) and xanthine-guanine phosphoribosyltransferase (gpt) cassettes.…”
Section: Methodsmentioning
confidence: 99%